A modified, mussel-inspired method to fabricate polyvinylidene fluoride membranes filled with halloysite nanotubes modified with dopamine, iron oxide, and silane for oil–water separation. (July 2019) - Zhang, Rui; Liu, Yi; Zhu, Xuyang; Cai, Youfeng; Li, Yu; Han, Qiong; Zhang, Tongqing
Polyvinylidene fluoride is an excellent membrane separation material, but its hydrophilicity is weak, which makes the membrane susceptible to contamination during use. In this study, a novel composite nanomaterial was prepared to improve the hydrophilicity of the polyvinylidene fluoride membrane, so that it can efficiently separate the oil–water emulsion. The nanophase material crystal structure was studied by X-ray diffraction, and the Fourier transform infrared spectroscopy revealed polar moieties (–OH, –NH2 ) on the membrane surface. The results show that the hydrophilic nanomaterials have been successfully prepared. The membrane surface morphology and the pore structure were analyzed by scanning electron microscopy and atomic force microscopy. It can be observed that the surface of the modified membrane is more orderly than the original polyvinylidene fluoride membrane. The polyvinylidene fluoride composite membrane's pure water flux was investigated by using a cup ultrafiltration device to characterize the permeability. The pure water contact angle was measured by a contact angle meter to characterize the membrane's hydrophilicity. The results show that the modified membrane has good hydrophilicity compared with the original polyvinylidene fluoride membrane. In addition, the oil–water separation performance was studied using four different types of oil/water emulsions. The experimental results showed that the membrane had a good performance in separating the emulsified oils with a highest oil removal rate of 97.2%. At the same time, the polyvinylidene fluoride membrane had good anti-fouling performance. After three pollution/washing cycles, the flux recovery rate still reached 84.6%. Under the long-term testing conditions, the performance of the membrane was relatively stable.